2022
DOI: 10.3847/1538-4357/ac6959
|View full text |Cite
|
Sign up to set email alerts
|

How Well Can We Measure Galaxy Dust Attenuation Curves? The Impact of the Assumed Star-dust Geometry Model in Spectral Energy Distribution Fitting

Abstract: One of the most common methods for inferring galaxy attenuation curves is via spectral energy distribution (SED) modeling, where the dust attenuation properties are modeled simultaneously with other galaxy physical properties. In this paper, we assess the ability of SED modeling to infer these dust attenuation curves from broadband photometry, and suggest a new flexible model that greatly improves the accuracy of attenuation curve derivations. To do this, we fit mock SEDs generated from the simba cosmological … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 80 publications
1
14
0
Order By: Relevance
“…Furthermore, the bias is pointed in a direction that supports our finding. However, for metallicity, Lower et al (2022) find that the bias and scatter are of the same order as the discrepancy we find, with the bias in a direction that weakens our finding. Therefore, we cannot make a firm statement about discrepancies in metallicity between the TNG100 model and reality without a follow-up study.…”
Section: Discussionsupporting
confidence: 60%
See 2 more Smart Citations
“…Furthermore, the bias is pointed in a direction that supports our finding. However, for metallicity, Lower et al (2022) find that the bias and scatter are of the same order as the discrepancy we find, with the bias in a direction that weakens our finding. Therefore, we cannot make a firm statement about discrepancies in metallicity between the TNG100 model and reality without a follow-up study.…”
Section: Discussionsupporting
confidence: 60%
“…For metallicity, Lower et al (2022) find a bias and scatter of 0.1-0.2 dex and ∼0.4 dex, respectively, with 50% of the galaxies within ∼0.25 dex. This bias and scatter is of a similar scale to the discrepancy we find of 0.28 dex.…”
Section: Dust-free Color Comparisonmentioning
confidence: 92%
See 1 more Smart Citation
“…Relevant to this project: differing ages, metallicities, and dust attenuation curves can produce similar effects in spectra, causing degeneracies (e.g., Conroy 2013;Santini et al 2015). In addition, Lower et al (2022) found that without FIR data, even though the bias introduced is negligible, dust attenuation curves of simulated galaxies are not as well constrained. As the photometry available for SED fitting is typically UV-NIR and possibly MIR, this leads to large uncertainties on attenuation parameters.…”
Section: Introductionmentioning
confidence: 97%
“…One of the most advanced models in this family is Prospector-α (Leja et al 2017). It incorporates galaxy properties including nonparametric star formation histories (SFHs; Leja et al 2019), selfconsistent nebular emission (Byler et al 2017), and a sophisticated dust model (e.g., Lower et al 2022), and critically, fits all parameters at once with Markov Chain Monte Carlo or nested sampling to produce joint high-dimensional constraints. Prospector-α has been designed specifically to extract the most information from high signal-to-noise photometry or spectra with good wavelength coverage.…”
Section: Introductionmentioning
confidence: 99%